The Dilemma of Local Democracy in Bali: Two Sides of Power in the Election of Perbekel - Piers Andreas Noak (Journal of Governance, 2024)
This article discusses the dilemma of selecting perbekel in Bali. There is an opportunity to break down the kinship system among the masses of voters, who are in the two realms of customary and official power. In this position, there is an interest bias. The bet on the mass of voters positions the two in a potential division. This article starts with the basic problem of how the two sides of power work in selecting equipment in Bali. This article departs from an analysis of the institutional rational choice theoretical frame, one of the approaches in political science. This article shows the perceptional aspect related to the potential dilemma of the working of local democracy in Bali, which is considered to include the polarization of power between traditional villages and service villages. This research is descriptive-qualitative in nature and involves conducting interviews with traditional village figures, elites, and government agencies. The results obtained only guarantee electoral accountability. The village dilemma is between two powers: domination power on the one hand and hegemonic power, as well as power relations in building patron-client relationships in the essence of selecting village heads, or perbekel. In reality, the practice of exercising power in villages in their original autonomous capacity is more hegemonic in nature. This condition then allows for such a strong network to exist between residents. On the one hand, psychologically, the development of this network is also colored by calculations of economic interests. It is this calculation of interests that often disrupts relationships between citizens. Both in the capacity of official villages and traditional villages, including the presence of vertical government.